To rearrange the equation \( A = \frac{1}{2}(b_1 + b_2)h \) for \( b_1 \), we need to isolate \( b_1 \) step by step.
Starting with the original equation:
-
Multiply both sides by \( 2 \) to get rid of the fraction: \[ 2A = (b_1 + b_2)h \]
-
Divide both sides by \( h \): \[ \frac{2A}{h} = b_1 + b_2 \]
-
Finally, subtract \( b_2 \) from both sides to solve for \( b_1 \): \[ b_1 = \frac{2A}{h} - b_2 \]
Thus, the correct rearrangement of the equation for \( b_1 \) is: \[ b_1 = \frac{2A}{h} - b_2 \]
This matches with the option:
b1 = 2Ah − b2
So, the correct response is: b1 = 2Ah − b2.